Development of students' cognitive motivation for studying English - Mishchenko, O.; Dmytryk, A. Yu. (KAD International, Ghana, West Africa, 2018)
The idiosyncrasies of developing motivation for learning English Language as a foreign language are revealed in the article. The authors emphasize that the question of how to help students to overcome the language barrier as soon as possible and to incite their interest for a foreign language is relevant and not completely resolved. As practice shows, foreign language teachers working at schools are in dire need of improving the communicative foreign language teaching methods and forming the interests and motives for learning the language among students. The authors give a description of modern aids of increasing students’ motivation to learn a foreign language, taking into account all the gains.
Keywords: foreign language; motivation; students; studying; motive